1994
DOI: 10.1002/mpo.2950230216
|View full text |Cite
|
Sign up to set email alerts
|

Primary cardiac angiosarcoma: A case report and review of therapeutic options

Abstract: A 45-year-old black patient presented with right-heart failure. Echocardiography showed a large tumor mass in the right atrium and a debulking procedure was performed. Histological and immunohistochemical studies revealed a high grade angiosarcoma infiltrating the myocardium and extending to the pericardial surface. Metastatic work-up showed no evidence of dissemination. The patient made an uneventful postsurgical recovery and was treated with chemotherapy, consisting of epidoxorubicin and dacarbazin. Followin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
4
0
1

Year Published

1997
1997
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 21 publications
0
4
0
1
Order By: Relevance
“…In two studies, patients had metastatic involvement at presentation in 66% and 89% of cases (5,6). There have been recent reports of survival from 12 to 30 months with some combination of chemotherapy, surgery, radiation therapy, and transplantation (10,16,17). Others studies have shown poor results with chemotherapy (18), and the overall experience with heart transplantation is poor (19,20).…”
Section: Introductionmentioning
confidence: 99%
“…In two studies, patients had metastatic involvement at presentation in 66% and 89% of cases (5,6). There have been recent reports of survival from 12 to 30 months with some combination of chemotherapy, surgery, radiation therapy, and transplantation (10,16,17). Others studies have shown poor results with chemotherapy (18), and the overall experience with heart transplantation is poor (19,20).…”
Section: Introductionmentioning
confidence: 99%
“…14 The most important cytostatics are Adriamycin, ifosfamid, or cyclophosphamide and dacarbazine accompanied by treatment with MESNA and, if necessary, G-CSF (granulocyte-stimulating factor). 14,18,19 Heart transplantation as treatment of primary cardiac soft tissue sarcoma is controversial. 3,16,20 Four patients with cardiac soft tissue sarcomas underwent heart transplantation followed by postoperative chemotherapy.…”
Section: Discussionmentioning
confidence: 99%
“…Frequent metastases are common and surgical excision often impossible due to extensive pericardial involvement [10]. Radiotherapy and surgery may offer some relief, but there is no clear evidence that they reduce mortality [8].…”
Section: Discussionmentioning
confidence: 99%
“…Two pathologic types of cardiac angiosarcoma have been described [8]. In the first type, the tumor is large, pedunculated, and protrudes into the right atrial cavity where it can cause obstruction of the tricuspid valve or the inferior vena cava.…”
Section: Discussionmentioning
confidence: 99%